2021
DOI: 10.1038/s41467-021-23716-6
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 binds TERRA RNA and suppresses R-Loop-based telomeric DNA damage

Abstract: R-loop structures act as modulators of physiological processes such as transcription termination, gene regulation, and DNA repair. However, they can cause transcription-replication conflicts and give rise to genomic instability, particularly at telomeres, which are prone to forming DNA secondary structures. Here, we demonstrate that BRCA1 binds TERRA RNA, directly and physically via its N-terminal nuclear localization sequence, as well as telomere-specific shelterin proteins in an R-loop-, and a cell cycle-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 64 publications
2
33
0
Order By: Relevance
“…Interestingly, this study showed that expression of RNaseH1 in IR-treated cells impaired BRCA1 recruitment to damage sites. An association between TERRA R-loops and BRCA1 was also recently described at telomeres and it was found that BRCA1 can associate directly with TERRA RNA through interactions mediated by the BRCA1 N-terminal NLS region ( Vohhodina et al, 2021 ). Binding of RNA via NLS sequences has been identified in other factors including the ribonuclease Dicer, which can be attributed to the density of positive charged amino acids in these regions that can facilitate binding to the ribonucleotide backbone ( LaCasse and Lefebvre, 1995 ).…”
Section: Rna:dna Hybrids In Double-strand Break Repairmentioning
confidence: 86%
See 1 more Smart Citation
“…Interestingly, this study showed that expression of RNaseH1 in IR-treated cells impaired BRCA1 recruitment to damage sites. An association between TERRA R-loops and BRCA1 was also recently described at telomeres and it was found that BRCA1 can associate directly with TERRA RNA through interactions mediated by the BRCA1 N-terminal NLS region ( Vohhodina et al, 2021 ). Binding of RNA via NLS sequences has been identified in other factors including the ribonuclease Dicer, which can be attributed to the density of positive charged amino acids in these regions that can facilitate binding to the ribonucleotide backbone ( LaCasse and Lefebvre, 1995 ).…”
Section: Rna:dna Hybrids In Double-strand Break Repairmentioning
confidence: 86%
“…Binding of RNA via NLS sequences has been identified in other factors including the ribonuclease Dicer, which can be attributed to the density of positive charged amino acids in these regions that can facilitate binding to the ribonucleotide backbone ( LaCasse and Lefebvre, 1995 ). The binding of TERRA by BRCA1 results in the suppression of TERRA transcription and promotes the repair or R-loop associated DNA damage at telomeres ( Vohhodina et al, 2021 ). The association of BRCA1 and R-loops at sites of DNA damage may also occur through NLS mediated interactions ( San Martin Alonso and Noordermeer, 2021 ).…”
Section: Rna:dna Hybrids In Double-strand Break Repairmentioning
confidence: 99%
“…Moreover, as previously mentioned, telomerase-negative ALT-positive cancer cells present higher levels of R-loops at their telomeres [ 79 ]. It has been recently reported that BRCA1 (Breast cancer gene 1) binds TERRA RNA as well as telomere-specific shelterin proteins in the R-loop, and in a cell cycle-dependent manner, suggesting that normal BRCA1/TERRA binding suppresses telomeric genome instability [ 101 ]. Additionally, BRCA2 deletion was reported to trigger TERRA overexpression and ALT mechanisms in colon cancer cells in the presence of telomerase activity [ 102 ].…”
Section: Terramentioning
confidence: 99%
“…Notably, these results are strikingly different from what has been seen for highly transcribed genes, which may retain R-loops from transcription and for which BRCA2 was reported to diminish R-loops through a collaboration with the TREX-2 mRNP biogenesis and export complex [ 35 ]. Interestingly, BRCA1 – which among others also promotes RAD51-mediated homologous recombination for DNA repair – is a second DNA recombination factor that was recently shown to physically interact with TERRA as well as TERRA R-loops [ 36 ]. In contrast to RAD51, however, BRCA1 counteracts telomeric R-loops [ 36 ].…”
Section: Terra R-loop Formation and Regulation At Chromosome Endsmentioning
confidence: 99%
“…Interestingly, BRCA1 – which among others also promotes RAD51-mediated homologous recombination for DNA repair – is a second DNA recombination factor that was recently shown to physically interact with TERRA as well as TERRA R-loops [ 36 ]. In contrast to RAD51, however, BRCA1 counteracts telomeric R-loops [ 36 ]. The underlying mechanism remains uncertain, but it was proposed to involve BRCA1 interactions with XRN2, which is the ortholog of yeast Rat1.…”
Section: Terra R-loop Formation and Regulation At Chromosome Endsmentioning
confidence: 99%